De nationalistiska Socialdemokraterna: En komparativ idéanalys av Socialdemokraternas partiprogram från 2013 och 2025 utifrån teorin om nationalism - Strömshed,Pixie; Lindbom,Noa (2026)
In recent years, research on European politics has increasingly examined a perceived turn toward nationalism, focusing largely on why this shift occurs and how it manifests. However, fewer studies address Swedish party politics and whether such nationalist tendencies can be identified in mainstream parties. Against this background, this thesis investigates whether nationalist ideas can be traced in the Swedish Social Democratic Party, a party typically positioned in opposition to explicitly nationalist political parties. To answer the research question, the Social Democrats’ party programmes from 2013 and 2025 are analysed and compared through an idea analysis drawing on an ideal type of nationalism, which provides the basis for an analytical framework applied to the material. The findings indicate a clear shift between the two programmes, with the 2025 programme containing more nationalist ideas than the 2013 programme. Such ideas are identified across all dimensions included in the ideal type. The thesis concludes by discussing the implications of these findings and suggesting directions for future research.
Keywords: Nationalism; Socialdemokraterna; partiprogram; Anthony D. Smith; Bonikowski